Theory of the price index : Fisher's test approach and generalizations - Eichhorn, Wolfgang; Voeller, Joachim (Berlin ; New York : Springer-Verlag, 1976)
This lecture notes described selected theories of price index. It covers: price indices depending only on prices; price indices depending on prices and quantities; price levels, price indices, and Fishers equation of exchange.
Includes index.
Includes bibliographical references: p. 83-87.
asm 23/01/2019
Loans
Keywords: Price indexes